A Hierarchically Ordered Array of Silver‐Nanorod Bundles for Surface‐Enhanced Raman Scattering Detection of Phenolic Pollutants. Issue 24 (26th April 2016) - Zhu, Chuhong; Meng, Guowen; Zheng, Peng; Huang, Qing; Li, Zhongbo; Hu, Xiaoye; Wang, Xiujuan; Huang, Zhulin; Li, Fadi; Wu, Nianqiang
Abstract : A hierarchically ordered array of Ag‐nanorod bundles is achieved using an inexpensive binary‐template‐assisted electrodeposition technique. In every bundle, many small gaps are formed between adjacent Ag‐nanorods, where "hot spots" are generated. As a result, this plasmonic nanostructure exhibits SERS enhancements of approximately eight orders of magnitude with uniform and reproducible SERS signal throughout the whole chip.